Cost of care for preterm babies in Jinja Regional Referral Hospital, East-central Uganda: A provider perspective - Ziyada Babirye; Elizabeth Kiracho Ekirapa; Goddie Geofrey Okeny; Angela Nakanwagi Kisakye; Freddie Ssengooba (Journal of Interventional Epidemiology and Public Health)
Introduction: Preterm birth and its complications are a major global health burden and significantly contribute to the under-five mortality in Uganda. This study aimed at identifying the morbidities suffered by preterm babies and the cost of preterm care to the provider in Jinja Referral Hospital.